Demographic Characteristics, Computer Self-efficacy and Internet Use by Undergraduates of Two Universities in South-west, Nigeria (2021)
The study examined demographic characteristics (age, gender, discipline, level of study) and Computer Self-efficacy (CS) as predictors of Internet Use (IU) by undergraduates of two universities in South-west, Nigeria. The survey design of correlational type was adopted, while the multi-stage sampling procedure was used to select a sample of 319 students. The instruments used were CS (α=0.76) and IU (α=0.71) scales. Data were analyzed using descriptive statistics, Pearson’s product moment correlation and Multiple regression at 0.05 level of significance. Undergraduates’ ages were mostly 21-25 years (49.3%), and 52.2% were male. They were mostly in 300 level-of-study (43.3%), with 37.4% being in the Science discipline. The most frequent useof the Internet was ‘online chatting’ ( =4.24), compared to the threshold mean value ( =3.00), while the greatest challenge was ‘high cost of the Internet Service Provider’ ( =3.16), compared to the threshold mean value ( =2.50). The level of computer self-efficacy was high, and CS (r=0.33) had significant relationship with IU. Demographic characteristics jointly predicted IU (F(4;269)=1.21; Adj.R2 =0.03), accounting for 3.0% of its variance. Demographic characteristics and CS jointly predicted IU (F(5;269)=8.36; Adj.R2 =0.12), accounting for 12.0% of its variance. Demographic characteristics and computer self-efficacy of undergraduates influenced their use of the Internet in south-west, Nigeria. These factors should be considered for improved use of the Internet among university students in the country.